PENGARUH HARGA, KEPERCAYAAN, KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN (STUDI PADA RENTAL MOBIL PT.MANDIRI CIPTA SEJAHTERA) - AHMAD MUHAMMAD NADLIF (Jurnal Manajerial, 2018)
This study aims to identify and analyze the effect of partial and simultaneous price, trust, and service quality on customer loyalty car rental services. PT.Mandiri Cipta Sejahtera branch of Gresik, sampling was done by using Accidental Sampling Teqnique that is by distributing 100 questionnaires. The analytical tool is to use multiple linear regression with the help of SPSS Windows V.15. Hypothesis testing using t test and f test with a significance level of 5%. The calculation results show that the three variables included in the analysis together have a significant influence on customer loyalty at PT.Mandiri Cipta Sejahtera branch of Gresik. This conclusion is based on calculations that show an F count of 12 151 for three F tables of 2,699 from these variables. It turns out that trust has a significant influence with a t value of 3.191 with a significance level of 2.5%. Based on the results of customer loyalty analysis at PT.Mandiri Cipta Sejahtera, the Gresik branch is very dominant in customer trust.